Antimicrobial activity of Latin American medicinal plant extracts - Haag, Griselda Octavia (2014)
Resistance of pathogenic microorganisms to several drugs has increased due to the widespread use of antibiotics to treat infectious diseases. Hence, development of new antimicrobial drugs from plants is an area of active research in the search for medicinal, veterinary or agricultural industry use. For this work 19 plants species was collected, dried in the shade and oven. 20 g powder plant were macerated in cold either with dichloromethane (DCM) or methanol (MeOH) filtered, evaporated to yield determination expressed in grams per 100g of dry plant. Methods: Antibacterial activity assays of the DCM and MeOH extracts were performed by agar diffusion. Paper disks were then impregnated with 10 ul of extract (range: 340-614mg/disc for MeOH; 300-500mg/disc for DCM). Solvents of DCM or MeOH extracts were used as negative controls (NC) and Gentamicin and Cephazoline were used as positive control (PC). The microorganisms used for testing were Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, and Pseudomonas aeruginosa ATCC 27853. The inoculum was incorporated to Petri plates and paper disks with extracts were added, and incubated for 24 hours at 37°C. Results: All DCM extracts tested except Gentianella parviflora, Baccharis crispa, Bauhinia candicans, Terminalia langiflora and Picrosia australis showed activity against Staphylococcus aureus. The DCM extracts of the three species of Gaillardia showed to be as well active against Escherichia coli. Only the MeOH extracts of Baccharis crispa, Gentianella achalensis, Lippia turbinata, Lippia germinata, Terminalia australis and bicolor adesmia were active against Staphylococcus aureus. Conclusion: dichloromethane extracts of Gaillardia and Protousnea poepiggii species might be important sources for the isolation of compounds with antimicrobial activity with a potential use in the pharmaceutical industry.